Causas de aborto diagnosticadas em fetos bovinos no estado de Mato Grosso - Ribeiro, Marlon (2023)
The state of Mato Grosso's beef cattle industry is a significant contributor to Brazil's agricultural economy. However, it faces challenges caused by reproductive failures that result in substantial losses. Investigating the causes of abortion in livestock in the state of Mato Grosso is fundamental to charactered diseases, particularly infectious ones that result in reproductive losses in this region. The study aims to characterize infectious diseases that resulted in abortions in the State of Mato Grosso performing necropsies of fetal products and the analysis of epidemiological, histopathological, microbiological, and molecular data. Two articles are described, one about a bovine abortion caused by Bacillus cereus and the other about three fetuses spontaneously aborted due to Ureaplasma diversum infection. Our results can help producers take appropriate measures to mitigate the risks of these diseases and ultimately increase their productivity. Therefore, it is crucial to continue studying and monitoring the causes of reproductive failures in cattle in the state of Mato Grosso to ensure the long-term sustainability of the beef cattle industry.